Plaque index of 7-year-old children at Coblong Public Elementary School (SDN) 1, 2, 3, 6 and Salman Al-Farisi Elementary School - Fajri, Wulan Desika; Setiawan, Asty Samiaty; Suryanti, Netty (Universitas Padjadjaran, 2014)
Introduction: Caries is the main oral cavity problem in children. One of the factors causing caries is dental plaque. The purpose of this research is to know the plaque index of 7-year-old children at Public Elementary School Coblong 1, 2, 3, 6 and Salman Al-Farisi Elementary School Bandung City in the year 2011. Method: The type of research is descriptive research with survey method. A total of 143 samples at Public Elementary School Coblong 1, 2, 3, 6 and 112 samples at Salman Al-Farisi Elementary School were obtained based on total sampling technique. Result: This research shows that the average plaque index of children age 7 years at Public Elementary School Coblong 1, 2, 3, 6 Bandung City in the year 2011 amounted to 1.37 and children age 7 years at Salman Al-Farisi Elementary School Bandung City in the year 2011 amounted to 0.74. Conclusions: Children aged 7 years in Public Elementary School Coblong 1, 2, 3, 6 and Salman Al-Farisi Elementary School Bandung City in 2011 has fair criteria of plaque index.